MODEL PENGEMBANGAN KOMPETENSI PENYULUH PERTANIAN DI PROVINSI GORONTALO - Ikbal Bahua; Marleni Limonu (University of Jember, 2016)
The purpose of this study was : (1) analyze internal factors that can formulate agricultural extension model of competence development in Gorontalo province, and (2) analyze the degree of relationship of internal factors that can formulate competency development model agricultural extension in Gorontalo. The research method is a survey method . To verify the model is done by using analytical SEM (Structural Equation Model) through the program LISREL (Linear Structural Relationships). The results show there is a direct influence while variable characteristics , motivation and self-reliance competence agricultural extension educator at each value : -0,30 ; 0,88, and 0,22 are significantly different at the level of α = 5 %, There are directions and coefficients relationships between variables, namely : the characteristic extension educator and motivation , as well as motivation and self-reliance extension educator. Coefficient of relationship between the variables : 0,50 and 0,25, which is significantly different at α = 0,05. Together these three variables influence the competency of agricultural extension workers by 0,74 units (74 %) were significant at α = 0,05. The proposed action plan for the first year is to conduct research in the field operationally through primary and secondary data collection and analyzing appropriate data analysis process, whereas in the second year research plan is to apply the model of competence development agricultural extension obtained in the study in the first year.